Impacts of non‐impacted third molar removal on the periodontal condition of adjacent second molars. (12th March 2020) - Sun, Li‐Juan; Qu, Hong‐Lei; Tian, Yi; Bi, Chun‐Sheng; Zhang, Shu‐Yin; Chen, Fa‐Ming
Abstract: Objective: The aim of this study was to determine how the removal of non‐impacted third molars (N‐M3s) affects the periodontal status of neighboring second molars (M2s). Subjects and Methods: The periodontal condition of M2s for which the neighboring N‐M3s were removed (more than 6 months previously) and those with intact N‐M3s was analyzed in a cross‐sectional observation study. In an additional case series, periodontal changes in M2s in response to adjacent N‐M3 removal were observed during a 6‐month follow‐up period. Results: A total of 457 patients with 1, 301 M2s were enrolled in this cross‐sectional observational study. Compared to M2s with neighboring N‐M3s, M2s without neighboring N‐M3s (teeth removed more than 6 months previously) exhibited a 0.27‐mm reduction in the average pocket depth (PD) ( p < .001) and a 0.38‐fold reduced risk of at least one probing site with PD ≥5 mm (PD5+) ( p < .001). Subsequently, a 41‐case follow‐up study showed that 6 months after neighboring N‐M3 extraction, the PD of the M2s decreased by 0.31 mm ( p < .001), while the incidence of PD5+ decreased by 21.9% when compared to the parameters detected before tooth extraction ( p = .004). Conclusions: Removing N‐M3s was associated with an improved periodontal condition in neighboring M2s.